Technical efficiency and financial performance in the Brazilian distribution service operators. (September 2017) - Altoé, Andrey Vinícius; da Costa Jr., Newton; Lopes, Ana Lúcia Miranda; Veloso, Thiago Roberto Magalhães; Saurin, Valter
Abstract: This paper analyses the relationship between technical efficiency, measured by Data Envelopment Analysis - DEA, and financial variables related to capital management in Brazilian distribution service operators (DSOs) from 2006 to 2009. The panel data regression showed that only firm size (measured by energy distributed) and previous year's income were statistically significant for explaining differences in technical efficiency. When companies invest part of their income, they are using "more expensive money" than if they are accessing other funding sources. It can therefore be seen that there is a possible margin for the Brazilian Distribution Service Operators DSOs to increase their leverage, which would reduce their cost of capital. This reduction in the cost of capital would in turn result in lower tariffs for the energy consumer, while maintaining the current calculation methodology.